PERANCANGAN BOOKLET PROMOSI WISATA WARISAN BUDAYA KABUPATEN TANAH DATAR - Raymond Armyn, Ir. Drs. Heldi, M.Si., Ph,.D. (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
Kabupaten Tanah Datar is rich in cultural tourism, because the history of the Minangkabau itself is common in the Tanah Datar district. The lack of optimalizing of information and communication about Tanah Datar cultural Heritage tourism cause of the lack of interest Visitors. On the observations, condition, and facts, effective, informative and interesting promotions are really needed, so there are no more confusion of tourists about the location of cultural Heritage tourism sites.The Booklet as the final work aims to design an interesting and informative information in order to attract tourists visit cultural heritage tours in Tanah Datar district and expectto able develop tourism in Tanah Datar district.The design method using the Glassbox method, this method of rational thinking that objectively and systematically examines things logically and is free of irrationall thoughts and considerations (irrational).Booklet design as the main media and supported by the bus branding media, an ojek helmet sticker branding, t-shirts, totebags,x-banners, mugs and stickers that are useful as supporting the main media.Keyword : Kabupaten Tanah Datar, Promotion, SWOT Analysis, Booklet